Catalysts of violence against women students: the role of the university, aggressors, and victims - Barbosa, Aline dos Santos; Romani-Dias, Marcello; Veludo-de-Oliveira, Tania (Frontiers in Psychology, 2024)
The purpose of this study is to bring a multilevel perspective to the discussion of the antecedents of violence against women in higher education settings.Originality/value: This paper was guided by the need indicated in the literature for research on the multiple levels that constitute the context of violence against women, as this is a public health problem, a designation that indicates the urgency with which this pervasive phenomenon should be addressed. The university context is conducive to this type of research, as it includes situations that favor instances of violence.Design/methodology/approach: This paper follows a qualitative and interpretative approach. This choice was due to the need to know the "how" and "why" elements that are part of violence against women in the university context. As the main source of evidence for the study, we conducted 20 in-depth interviews with women (victims) and men (aggressors), all university students involved in situations of violence. The transcription of the interviews generated 346 quotations, including 41 analysis codes.Findings: After conducting the data coding, we identified that (i) the actions and omissions of the educational institution, (ii) the taste for violence, the perception of self-efficacy and the influence of the aggressors' group of friends, and (iii) the apparent dichotomy between women's vulnerability and women's strength are among the main antecedents of violence against women. The article concludes with possible research questions to combat violence. Among the contribution of the discussions presented in our article, we highlight the importance of adopting a multilevel view so that we can better understand and fight against this violence, the existence of which is not restricted to the university context.